FGF19 subfamily members: FGF19 and FGF21 - Dolegowska, Katarzyna (J Physiol Biochem, 2019)
Fibroblast growth factors (FGF) constitute a large family of proteins with pleiotropic effects on development, organogenesis, and metabolism. The FGF19 subclass includes growth factors circulating with the blood referred to as endocrine FGF. Representatives of the FGF19 subclass, including FGF19, FGF21, and FGF23, act via FGFR receptors. The proteins of FGF19 subfamily influence the enterohepatic circulation of bile, participate in glucose and lipid metabolism regulation, and maintenance of phosphorus and vitamin D3 homeostasis. FGF19 and FGF21 are activated under different physiological and pathological conditions.